Studi Epidemiologi Perkembangan Prehipertensi Menjadi Normotensi, Tetap Prehipertensi, Hipertensi Stage I dan Stage II Setelah 10 Tahun - Alatas, HAIDAR (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2020)
Abstract Individual with a systolic BP of 120 to 139 mmHg or diastolic BP of 80 to 89 mmHg should be considered as prehypertensive and require health-promoting lifestyle modifications to prevent CVD. After four years, 40% of prehypertension that is not managed properly becomes serious hypertension. Approximately 31â€“37% of US adults are prehypertensive, is associated with 3-fold greater likelihood of developing hypertension and roughly twice the cardiovascular events. What is the progress of prehypertension after 10 years in rural populations? Will it be normal (normotensive), still prehypertension, become stage I hypertension or stage II hypertension. Epidemiological studies were conducted in Mlati Village, Sleman, Yogyakarta. From the prehypertension subject data as many as 4,091 who were on the computer, after 10 years were selected who were still aged 30-59 years, were willing to take further research and then do interviews and blood pressure checks. The data obtained was analyzed. Of the 743 subjects now aged 30-59 years, who had prehypertension ten years ago, their blood pressure became normal as many as 183 (25%), still prehypertension was 328 (44%), became stage I hypertension as much as 152 (20%) and became hypertensive stage II as many as 80 (11%). Â Â Abstrak Prehipertensi menurut JNC 7 adalah tekanan darah 120-139/80-89 mmHg. Dalam 4 tahun, 40% prehipertensi dilaporkan akan menjadi hipertensiÂ yang serius bila tidak dikelola dengan baik. Sekitar 31-37% populasi di Amerika Serikat dewasa merupakanÂ penyandang prehipertensi dan berhubungan dengan kecenderungan tiga kali lipat untuk mengalami hipertensi dan dua kali lipat untukÂ mengalami kejadian kardiovaskular dibanding orang dengan tekanan darah normal. Bagaimana perkembangan prehipertensi setelah 10 tahun pada populasi daerah pedesaan? Apakah akan menjadi normal (normotensi), tetap prehipertensi, menjadi hipertensi stage I atau hipertensi stage II. Dilakukan studi epidemiologi di Desa Mlati, Sleman, Yogyakarta. Dari data subyek prehipertensi sebanyak 4.091 yang ada di komputer, setelah 10 tahun dipilih yang masih berusia 30-59 tahun, bersedia mengikuti penelitian lanjutan kemudian dilakukan wawancara dan pemeriksaan tekanan darah. Data yang didapatkan dianalisis. Dari 743 subyek sekarang berusia 30-59 tahun, yang sepuluh tahun lalu prehipertensi, didapatkan tekanan darahnya menjadi normal sebanyak 183 (25%), tetap prehipertensi sebanyak 328 (44%), menjadi hipertensi stage I sebanyak 152 (20%) dan menjadi hipertensi stage II sebanyak 80 (11%). Â